Does the incorrect classification of misconduct charges constitute substantive unfairness? EOH Abantu v CCMA (2019) 40 ILJ 2477 (LAC) - Newaj, Kamalesh (Obiter, 2020)
Dismissals are commonplace in employment and arise for various reasons. One such reason is the unacceptable or undesirable conduct of an employee, which is recognised as a dismissal for misconduct. Notwithstanding the employers’ right to effect dismissals, employees are considerably protected by the law (s 185 of the Labour Relations Act (LRA)). An employee has the right to challenge his/her dismissal by referring an unfair dismissal dispute to the CCMA (s 191 of the LRA). This is not surprising considering the fact that fairness is the cornerstone of the employment relationship (as evident from s 23(1) of the Constitution, which states that “everyone has the right to fair labour practices”; see also Blanpain and Weiss Changing Industrial Relations and Modernisation of Labour Law (2003) 182). While it is indisputable that employers should act fairly towards its employees, a significant principle that has been highlighted in the determination of fairness is that it must accommodate and balance the conflicting interests and rights of both employers and employees (National Education Health & Allied Workers Union v University of Cape Town (2003) 24 ILJ 95 (CC) par 38 and 40).